Q: What is m 2?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

-m2+3m-2 -m2+2m+m-2 -m(m -2)+1(m-2) (-m+1)(m-2) or

factor by grouping 7m(m-2)+6n(2-m)

m-2

2m^2 - 8 = 2(m^2 - 4) = 2(m-2)(m+2). A difference of squares, x^2 - y^2 say (or m^2 - 2^2 above), factorises as (x - y)(x + y).

If: m/8 -2 = 48 Then: m = 400

Related questions

5(m-2) - m(m-2)

(m-2)/(m+2) * m/(m-1) = [(m-2)*m]/[(m+2)*(m-1)] = (m2 - 2m)/m2 + m - 2)

5(m-2) - m(m-2)

m+m when m equals 2. 2+2 4

( m^2 - m - 3 ) + ( m - 4 ) = m^2 - m - 3 + m - 4 = m^2 - 7Answer: m^2 - 7

-m2+3m-2 -m2+2m+m-2 -m(m -2)+1(m-2) (-m+1)(m-2) or

m + 9 = 2 Therefore, m = 2 - 9 m = -7

factor by grouping 7m(m-2)+6n(2-m)

Let the numbers be m & m+1 (consecutive) Hence their squares are m^2 & ( m + 1)^2 => m^2 & m^2 + 2m + 2 Hence Their sum is m^2 + m^2 + 2m + 1 = 85 2m^2 + 2m - 84 = 0 m^2 + m - 42 =0 Factor (m + 7)(m - 6) = 0 Hence the numbers are 6 & 7 .

Let the number be 'm' & 'm + 2' Hence their squares are m^2 & (m+2)^2 There sum is m^2 + (m+2)^2 = 340 Multiply out he brackets m^2 + m^2 + 4m + 4 = 340 . 2m^2 + 4m + 4 = 340 Divide both sides by '2' m^2 + 2m + 2 = 170 m^2 + 2m - 168 = 0 Factor (m - 12)(m + 14) = 0 Hence m = 12 & m+ 2 = 14 The two consecutive even numbers. 12^2 = 144 14^2 = 196 144 + 196 = 340 As required.

if by m2 you mean m multiplied by 2, then m= 2 2/3if by m2 you mean m squared, then m still =2 2/3, because the m squared becomes m times m which equals 2m

6